The protomédic Miguel Tafur - Lastres, Juan B. (1954)
Miguel Tafur and Zea as Paredes was born in Lima on September 29, 1766, eleven years after Unanue and 8 Dávalos. They were successful in running the country Viceroy Don Manuel de Amat y Junient (1761-1776), who cared anything for higher education and to expel the Jesuits played (27 February 1767), transcendent event in the years peaceful colonial life.